Neurofeedback Control of the Human GABAergic System Using Non-invasive Brain Stimulation. (1st June 2018) - Koganemaru, Satoko; Mikami, Yusuke; Maezawa, Hitoshi; Ikeda, Satoshi; Ikoma, Katsunori; Mima, Tatsuya
Highlights: GABA is a major inhibitory neurotransmitter in the central nervous system. Short intracortical inhibition (SICI) indices GABAergic activities in M1. Neurofeedback learning based on SICI was done in healthy subjects. The SICI feedback learning resulted in a significant enhancement in SICI. It suggests that we could intrinsically control GABAergic activities in M1. Abstract: Neurofeedback has been a powerful method for self-regulating brain activities to elicit potential ability of human mind. GABA is a major inhibitory neurotransmitter in the central nervous system. Transcranial magnetic stimulation (TMS) is a tool that can evaluate the GABAergic system within the primary motor cortex (M1) using paired-pulse stimuli, short intracortical inhibition (SICI). Herein we investigated whether neurofeedback learning using SICI enabled us to control the GABAergic system within the M1 area. Forty-five healthy subjects were randomly divided into two groups: those receiving SICI neurofeedback learning or those receiving no neurofeedback (control) learning. During both learning periods, subjects made attempts to change the size of a circle, which was altered according to the degree of SICI in the SICI neurofeedback learning group, and which was altered independent of the degree of SICI in the control learning group. Results demonstrated that the SICI neurofeedback learning group showed a significant enhancement in SICI. Moreover, this group showed a significant reduction in choice reaction time compared to the control group. Our findings indicate that humans can intrinsically control the intracortical GABAergic system within M1 and can thus improve motor behaviors by SICI neurofeedback learning. SICI neurofeedback learning is a novel and promising approach to control our neural system and potentially represents a new therapy for patients with abnormal motor symptoms caused by CNS disorders.